Promotional Strategy Planning for Nglanggeran Agricultural Technology Park in Gunungkidul Regency - Arozy, Syahrial Khais; Widowati, Indah (Jurnal Dinamika Sosial Ekonomi, 2025)
This study aimed to 1) analyze the internal and external factors of Nglanggeran Agricultural Technology Park based on the promotion mix, 2) analyze an appropriate promotion strategy to increase the sales of chocolate processed products in Nglanggeran Agricultural Technology Park. This research is carried out through quantitative descriptive methods with a case study type of research. The method of determining respondents is purposive. The data types used are primary data and secondary data. Data collection is done through questionnaires, interviews, Focus Group Discussions, observations, and documentation. The analytical techniques used are Internal Factor Evaluation (IFE), external factor evaluation (EFE), internal external matrix (IE), SWOT matrix, and the Quantitative Strategic Planing Matrix (QSPM). The results of the research showed that 1) the main internal strength factor is the opening of an educational and manufacturing training visit program, while the main weakness factor is a lack of workforce in the promotion section. The primary external factor of opportunity is the existence of cooperative relations with external parties, whereas the primary threat factor is competition with other manufacturers of processed chocolate products. 2) The appropriate promotion strategy to increase the sales of processed chocolate products is by doing brand activation.